Renal dysfunction in methylmalonic acidurias: review for the pediatric nephrologist - Morath, Marina; Hörster, Friederike; Sauer, Sven (Pediatric nephrology, 2013)
Methylmalonic acidurias are a heterogeneous group of inborn errors of branched-chain amino acid metabolism. Depending on the underlying etiology, acute or chronic renal disease constitutes major (long-term) complications. In recent decades, overall survival has improved due to optimized treatment strategies based on the use of standardized emergency protocols and dialysis techniques. The majority of these patients, especially those having mut°, cblB, and cblA deficiency, are at increased risk of developing chronic kidney disease secondary to tubulointerstitial nephritis to require hemo- or peritoneal dialysis. Kidney and/or liver transplantation, as organ replacement, or even gene therapy on a limited scale, are controversially discussed treatment options in methylmalonic acidurias. The pathophysiological basis of renal disease has not been clarified in detail until now, but a severe mitochondrial dysfunction and an impairment of tubular dicarboxylic acid transport due to accumulated toxic metabolic compounds has been recently proposed. Another severe renal complication of methylmalonic acidurias is the occurrence of cblC-associated infantile atypical hemolytic syndrome, which can result in acute kidney injury. Close collaboration between (pediatric) nephrologists and metabolic specialists is required for the long-term management of these patients.